DEVELOPMENT OF A FIVE TIER DIAGNOSTIC TEST OF MISCONCEPTIONS ON CHEMICAL EQUILIBRIUM MATERIAL - Saputra, Anwar; Parbuntari, Hesty (MO.RI Publishing, 2025)
Misconceptions in learning chemistry have the potential to have a negative impact because of the close interrelationship of chemical materials. This study aims to develop an effective five-level diagnostic test to identify students' misconceptions in the topic of chemical equilibrium. Through the R&D approach and Rasch model. Data from validation by experts (3 chemistry lecturers and 2 high school teachers) were processed using Minifac software. Furthermore, the raw data from the pilot test on 32 students were analyzed with Ministep software. The results of the analysis showed that the research instrument had good content validity, sufficient to very good reliability (0.70-0.86), the analysis of the difficulty index showed that the questions at the first and third levels had four categories of difficulty, while at the fifth level there were three categories. The differentiated power of the questions also showed a similar pattern, with four categories in the first and third levels and three categories in the fifth level.